SINFONI - Integral Field Spectroscopy at 50 milli-arcsecond resolution with the ESO VLT - Eisenhauer, F; Bonnet, H; Abuter, R; Bickert, K; Bianca-Marchet, F; Brynnel, J; Conzelmann, R; Delabre, B; Donaldson, R; Farinato, J; Fedrigo, E; Finger, G; et al. (2003)
SINFONI is an adaptive optics assisted near-infrared integral field spectrometer for the ESO VLT. The Adaptive Optics Module (built by the ESO Adaptive Optics Group) is a 60-elements curvature-sensor based system, designed for operations with natural or sodium laser guide stars. The near-infrared integral field spectrometer SPIFFI (built by the Infrared Group of MPE) provides simultaneous spectroscopy of 32 x 32 spatial pixels, and a spectral resolving power of up to 3300. The adaptive optics module is in the phase of integration; the spectrometer is presently tested in the laboratory. We provide an overview of the project, with particular emphasis on the problems encountered in designing and building an adaptive optics assisted spectrometer.